1999
DOI: 10.1093/pasj/51.6.791
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Clouds and Star Formation in the Southern H II Regions

Abstract: We have carried out extensive 13CO(J = 1−0) observations toward 23 southern H II regions associated with bright-rimmed clouds. In total, 95 molecular clouds have been identified to be associated with the H II regions. Among the 95, 57 clouds \ are found to be associated with 204 IRAS point sources which are candidates for young stellar objects. There is a significant increase of star-formation efficiency on the side facing to the H II regions; the luminosity-to-mass ratio, defined as the ratio of the stellar l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
96
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(109 citation statements)
references
References 0 publications
10
96
3
Order By: Relevance
“…Yamaguchi et al (1999) Shock speeds derived from observations are similar. White et al (1999) and Thompson et al (2004) derived shock velocities from pressure in pre-and post-shock regions.…”
Section: Comparison With Observationsmentioning
confidence: 80%
“…Yamaguchi et al (1999) Shock speeds derived from observations are similar. White et al (1999) and Thompson et al (2004) derived shock velocities from pressure in pre-and post-shock regions.…”
Section: Comparison With Observationsmentioning
confidence: 80%
“…Molecular line observations toward RCW 38 are very limited. Yamaguchi et al (1999) observed a large area of RCW 38 in the 13 CO J = 1-0 emission with NANTEN and found a molecular cloud at 2-3 km s −1 that coincides with IRS 2, although detailed structures including the ring-like component were not resolved due to a relatively coarse resolution. On the other hand, Zinchenko et al (1995) observed the central region of RCW 38 at a half-power beam width (HPBW) of ∼1′ in the CS emission to resolve the ring shape surrounding IRS 2.…”
Section: Rcw 38 As the Youngest Super Star Cluster In The Milky Waymentioning
confidence: 99%
“…The HII regions, their ionising star(s), heliocentric distances and associated BRCs are listed in Table 1. The ionising star(s), spectral types and assumed distances are drawn from Yamaguchi et al (1999) and Thompson et al (2004b) and references therein, apart from σ Sco where the spectral type and assumed distance are taken from Eggen (1998). The spectral types of HD 305938, CCDM J16212−2536AB, HD 326286 and HD 152245 have been drawn from SIMBAD.…”
Section: Southern Catalogue Of Brcsmentioning
confidence: 99%
“…The Gum Nebula is located at a heliocentric distance of ∼450 pc and covers a region of 30 • × 30 • (Sugitani & Ogura 1994 and references therein). It is excited by two stars, ζ Pup and γ 2 Vel, which have spectral types O4 If and WC 8+O8 III respectively (Yamaguchi et al 1999). There are six BRCs associated with Gum nebula (SFO 46,48,(50)(51)(52)(53), only one of which is located within the MSX survey region (SFO 51).…”
Section: The Gum Nebulamentioning
confidence: 99%